Association of Increased Indoleamine 2, 3‐Dioxygenase With Impaired Natural Killer Cell Activity in Hemodialysis Patients. Issue 1 (4th July 2013) - Tanaka, Asuka; Kato, Akihiko; Suzuki, Yuzo; Suzuki, Masako; Ohmori, Hiromitsu; Sumimoto, Ryo; Ohdan, Hideki
Abstract Indoleamine 2, 3‐dioxygenase (IDO) suppresses adaptive immune response. However, there was no study to examine whether IDO activity is associated with immune parameters in dialysis patients. In this study, we estimated serum IDO activity by the kynurenine/tryptophan ratio (KTR), and compared KTR with natural killer (NK) cell activity, soluble interleukin‐2 receptor (sIL‐2R) and serum levels of trace elements such as selenium (Se) and zinc (Zn) that affect T‐cell function in 28 hemodialysis (HD) patients (age: 72 ± 13 years old, time on HD: 79 ± 89 months). NK cell activity was decreased in 35.7% of the patients. KTR values were almost 10‐times higher in HD patients (380.81 ± 385.46 mM/M) than those in the referred controls (32.9 ± 9.10 mM/M). KTR was lower in patients with impaired NK cell activity than those without (279 ± 111 vs. 565 ± 603 mM/M, P = 0.07). There was no relationship between KTR and sIL‐2R and Zn, while KTR was significantly and negatively correlated with serum Se levels that can impair cellular immunity (r = −0.41, P < 0.05). Our findings suggest that increased IDO activity with Se deficiency may be associated with impaired NK cell function in HD patients.